Implementasi Business Intelligence pada Sistem Informasi Backstore Berbasis Web untuk Monitoring Operasional Toko Ritel - Mirza Fatqul Zailani; Yoseph Tajul Arifin; Rizky Ade Safitri (INFORMATION SYSTEM FOR EDUCATORS AND PROFESSIONALS : Journal of Information System, 2026)
Operational management in modern retail stores requires an information system capable of supporting fast, accurate, and integrated data monitoring. However, operational data management in some retail stores is still conducted separately using spreadsheets, resulting in low data integration, delays in information presentation, and limited real-time monitoring capabilities. This study aims to implement Business Intelligence in a web-based backstore information system to support centralized and data-driven retail operational monitoring. The research employed the Waterfall software development approach, which was selected because the system requirements had been clearly identified, allowing the development process to be carried out systematically through the stages of requirements analysis, system design, implementation, testing, and evaluation. The system was developed using PHP, the CodeIgniter 3 framework, MySQL database, and the Model-View-Controller (MVC) architecture. The implementation of Business Intelligence was carried out through a visual dashboard displaying integrated operational indicators, including sales data, keepstock, damaged goods, stock checklist, and petty cash. System testing using the Blackbox Testing method showed that all system functions operated according to user requirements. The results indicate that the system successfully improved operational data integration, accelerated monitoring and data recapitulation processes, and supported more effective and real-time data-driven decision-making within retail store operations.